2013
DOI: 10.1089/jpm.2012.0475
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved Caregivers as Educators in Pediatric Palliative Care: Their Experiences and Impact

Abstract: Background: With the continuing growth of pediatric palliative care, there is an increasing need to develop effective training for health care professionals. Bereaved parents have participated in the training of health care professionals utilizing curriculum from the Initiative for Pediatric Palliative Care (IPPC), but the experience of bereaved parents as educators has not been studied. Objectives: This qualitative research examined the experience of bereaved parents involved in pediatric palliative care educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
2
11
0
2
Order By: Relevance
“…Parents reported that this training program provided them with an invaluable opportunity to enhance their child's legacy by teaching future physicians the requisite skills by which to improve communication with patients and families. Our findings corroborate prior research in which bereaved parents played a beneficial role in the training of care providers, 29 and further suggest that the participation of bereaved parents in educational sessions may contribute to positive grief adjustment and facilitate meaning-making for bereaved parent educators as well.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Parents reported that this training program provided them with an invaluable opportunity to enhance their child's legacy by teaching future physicians the requisite skills by which to improve communication with patients and families. Our findings corroborate prior research in which bereaved parents played a beneficial role in the training of care providers, 29 and further suggest that the participation of bereaved parents in educational sessions may contribute to positive grief adjustment and facilitate meaning-making for bereaved parent educators as well.…”
Section: Discussionsupporting
confidence: 89%
“…Previous work with this and other groups of bereaved parents has revealed that telling their child's story is an important component of personal bereavement and meaning‐making : “…You find things that, through your grief journey, hopefully, you can find things that bring meaning to what you've experienced and what you've been through.” Parents reported that this training program provided them with an invaluable opportunity to enhance their child's legacy by teaching future physicians the requisite skills by which to improve communication with patients and families. Our findings corroborate prior research in which bereaved parents played a beneficial role in the training of care providers, and further suggest that the participation of bereaved parents in educational sessions may contribute to positive grief adjustment and facilitate meaning‐making for bereaved parent educators as well.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, some follow‐up efforts have been perceived as inadequate, suggesting the importance of training staff. In addition, involving bereaved parents in developing and administering bereavement education programs and interventions has been shown to have great value for them, further giving meaning to their child's life …”
Section: Resultsmentioning
confidence: 99%
“…Bereaved parents have been utilized in educating health-care professionals in several settings, including being a part of a parent panel at conferences, or participating in facilitated, small-group discussions with staff. 56 , 59 62 While most family members have been parents who have experienced the death of a child, grandparents and siblings have also participated. A study examining a program that utilized bereaved parents in an 8-week luncheon training series for health-care providers was evaluated to study motivations, expectations, challenges, benefits, and meaning-making.…”
Section: Training Interventions: Instructional Strategiesmentioning
confidence: 99%